2008
DOI: 10.1002/app.29205
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of superfine down powder

Abstract: Superfine down powder was produced from down fiber after it was cut into short pieces and ground on a purpose-built machine. Scanning electron microscopy photographs showed that the down fiber was ground into particles with some fiber fragments and a large amount of rod-shaped ultrafine powder. Particle size distribution analysis indicated that the average size of the down powder was 1.546 lm. Fourier transform infrared analysis showed that the absorbing peaks around 1640, 1520, and 1230 cm À1 were sharper tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…We noted that the NSNDPs exhibited a white colour just like that of natural down fibres (Figure 1c), which suggested that the native properties of the down fibres were not adversely affected and were preserved well during the manufacturing process. The results were consistent with results previously reported in the literature [16,19]. Further, it can be seen that most of the NSNDPs had diameters of 1-2 lm and aspect ratios of 20-100.…”
Section: Resultssupporting
confidence: 92%
“…We noted that the NSNDPs exhibited a white colour just like that of natural down fibres (Figure 1c), which suggested that the native properties of the down fibres were not adversely affected and were preserved well during the manufacturing process. The results were consistent with results previously reported in the literature [16,19]. Further, it can be seen that most of the NSNDPs had diameters of 1-2 lm and aspect ratios of 20-100.…”
Section: Resultssupporting
confidence: 92%
“…The active groups of the zirconium oxychloride and down fibers combined firmly via chemical bonding, which imparted the modified down with a durable warmth retention property. The two spectra exhibit similar absorption bands at approximately 3281 (N-H and O-H), 2923 (-CH 2 ), 1633 (amide I), 1516 (amide II), and 1236 cm -1 (amide III) [23]. Therefore, the modification does not destroy the surface structure of the down fiber, and its natural shape remains intact.…”
Section: Ftir Analysis Of Modified Downmentioning
confidence: 92%
“…Furthermore, down feather dimensions (highly order, hierarchical branched structures) make it unsuitable for producing thermoplastic protein films. In this context, down feather was cut into small pieces of fiber and then ground into down feather fiber (SDP), which has the size distribution between 0.2-12μm and the average particle size of 2.34μm [12]. Based on our previous study, down feather fiber has nearly 14 times the specific surface area of down feather and was blended with polypropylene and polyurethane respectively [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%